Willingness to Receive COVID-19 Vaccination for Children Under Five Years in Jakarta - Devia, Mutiara; Utami, Aras; Pramono, Dodik; Pratiwi, Rina (Jurnal Kesehatan Masyarakat, 2023)
Indonesia reached the highest number of deaths caused by COVID-19 in children under five years, and the cases continued to rise to 10.6% in February 2022. Vaccination is an effective way to deal with the COVID-19 pandemic. The risk of its infection in children under five years has been underestimated, and parent’s hesitancy still becomes an obstacle. This study aimed to identify factors associated with willingness to receive COVID-19 vaccination for children under five years among parents based on the Health Belief Model. A cross-sectional study was held in Jakarta from August 1st – 20, 2022. A total of 173 parents with children under five years (0-59 months) were taken using the consecutive sampling method, and data were taken with self-reported online and printed questionnaires. Chi-square bivariate and binary logistic regression multivariate analysis were used to determine the association. Adjusted odds ratios (OR) and 95% confidence intervals (CIs) were presented, and statistical significance was set at p 0.05. Parent’s willingness level to get COVID-19 vaccination for their children was 68.8%. The multivariate analysis revealed that perceived benefit (p=0.045; OR=2.784; 95%CI=1.023-7.579) and cues to action (p0.001; OR= 23.144; 95%CI= 8.577-62.453) were predictors of parent’s willingness to receive COVID-19 vaccine for their children.